Sie sind auf Seite 1von 5

# www.sakshieducation.

com

LENGTHS OF TANGENT, NORMAL, SUBTANGENT AND SUB NORMAL Definition : Let y = f ( x ) be a differentiable curve and P be a point on the curve. Let the tangent and normal at P to the curve meet the x - axis in T and N respectively. Let M be the projection of P on the x - axis. Then (i) PT is called the length of the tangent, (ii) PN is called the length of the normal, (iii) TM is called the length of the subtangent, (iv) MN is called and length of the subnormal at the point P.

Let P( x1 , y1 ) be a point on the curve y = f ( x ) . Then (i) the length of the tangent to the curve at P is

y1 1 + m2 . m

(ii) the length of the normal to the curve at P is y1 1 + m 2 . (iii) the length of the subtangent to the curve at P is

y1 . m

## (iv) the length of the subnormal to the curve at P is y1m

dy where m = . dx P

www.sakshieducation.com

www.sakshieducation.com
Exercise 1. Find the length of sub-tangent and sub normal at a point of the curve y = b.sin . Sol: Equation of the curve is y = b.sin
Let P(x,y) be a point on the curve.
x b.sin y1 a = a. tan x Length of the sub-tangent = = b x m a .cos a a
x a

x dy x 1 b x = b.cos . = .cos =m a dx a a a a

## x b x b2 2x . Length of the sub-normal = y1m = b.sin . cos .sin = a a a 2a a

2.

Show that the length of sub-normal at any point on the curve xy = a2 varies as the cube of the ordinate of the point.

## Sol: Equation of the curve is xy = a2.

a2 y= x
dy a 2 =m = dx x 2

## Let P(x,y) be a point on the curve. ( a ) 2 y2 Length of the sub-normal = y1m = y1 2 = a 2 y1 1 x1 a4

=
3 y1 3 y1 = cube of the ordinate.

3.

Show that at any point (x, y) on the curve y = be x / 3 , the length of the subtangent is constant and the length of the sub-normal is
y2 . a

## Sol: Let P(x,y) be a point on the curve.

Equation of the curve is y = be x / 3
dy 1 y =m = b.e x / 3 . = dx a a

www.sakshieducation.com

www.sakshieducation.com
Length of the sub-tangent

y1 y = = a = constant m y a

## Length of the sub-normal y1m =y.y/a=y2/a

4.

Find the value of k so that the length of the sub-normal at any point on the curve x.y k = ak +1 is constant. ?

## Sol: Let P(x1,y1) be a point on the curve.

Equation of the curve is x.y k = a k +1 . Differentiating w.r.to x
x.k.y k 1 dy + y k .1 = 0 dx dy = yk dx

k.xy k 1.

## Length of the sub-normal = y1m = y1

2 k k +2 y1 y1 y1 = . k +1 = k a k.a k +1

Length of the sub-normal is constant at any point on the curve is independent of x1 and

y1k + 2 is independent of y1 k + 2 = 0 k = 2 k .a k +1

www.sakshieducation.com

www.sakshieducation.com
5. At any point t on the curve x = a (t + sin t), y = a(1 cos t). Find the lengths of the tangent, normal, sub-tangent and sub-normal.

## Sol: Equation of the curve is x = a (t + sin t), y = a(1 cos t)

dy dy a sin t dt = = dx dx a (1 + cos t ) dt
t t t 2 sin .cos sin 2 2= 2 =m = t 2 t 2 cos cos 2 2 = a (1 cos t ) 1 + cot 2 t 2

y1 1 + m2 m

## t t t t 1 = 2a.sin 2 .cos ec = 2a sin = 2a.sin 2 . 2 2 2 2 sin t 2

Length of the normal y1 1 + m 2 = a (1 cos t ) 1 + tan 2
t 2

t 2 t = a a sin .sec 2 2

## Length of the sub-normal y1m = a (1 cos t )

= 2a sin 2 t / 2.tan t / 2 = 2a sin 2 t / 2.tan t / 2

sin t / 2 cos t / 2

www.sakshieducation.com

www.sakshieducation.com
6. Find the length of normal and sub-normal at a point on the curve y =
a x/a + e x / a . e 2

## Sol: Equation of the curve is y =

a x/a + e x / a e 2

x = a.cosh a

## dy x x1 = a.sinh = sinh =slope of tantent at any point =m dx a a a

= a.cosh x a 1 + sinh 2 x a

## Length of the normal y1 1 + m 2

x x x = a.cosh .cosh = a.cosh 2 a a a

## Length of the sub-normal y1m

= a x x 2 sinh .cosh 2 a a

x x = a.cosh .sinh a a

a 2x .sinh 2 a

7.

Find the length of the sub-tangent and sub-normal of a point t o the curve x = a ( cos t + t sin t ) y = a ( sin t t cos t ) .

Sol:

## Equation of the curve are x = a ( cos t + t sin t ) , y = a ( sin t t cos t )

dy at sin t dy dt = = = tan t dx dx at cos t dt

## Length of the sub-tangent =

= a cot t ( sin t t cos t )

## Length of the sub-normal = y1.f `( x1 )

= a ( sin t t cos t ) tan t = a tan t ( sin t t cos t )

www.sakshieducation.com